Leukocytes Detection, Classification and Counting in Smears of Peripheral Blood - Martínez - Castro, J.; Reyes - Cadena, S.; Felipe - Riverón, E. (Revista Mexicana de Ingenieria Biomedica, 2014)
Using the k-NN classifier in combination with the first Minkowski metric, in addition to techniques of digital image processing, we developed a computational system platform-independent, which is able to identify, to classify and to count five normal types of leukocytes: neutrophils, eosinophils, basophils, monocytes and lymphocytes. It is important to emphasize that this work does not attempt to differentiate between smears of leukocytes coming from healthy and sick people; this is because most diseases produce a change in the differential count of leukocytes rather than in their forms. In the other side, the system could be used in emerging areas such as the topographic hematology and the chronobiology.